Resiliensi Muslim Ditinjau Dari Perspektif Psikologi Tasawuf - Denise Adrian (Jurnal Budi Pekerti Agama Islam, 2024)
This research employs a literature review method aimed at exploring the development of resilience and how Sufi psychology can strengthen individual resilience. The findings indicate that one of the primary factors in Muslim resilience, according to Sufi psychology, is deep faith. Spiritual practices such as dhikr and prayer, along with social support from the community, play a crucial role in building mental and emotional resilience. The implications of this study suggest that integrating Sufi values into strategies for dealing with adversity can provide valuable guidance for Muslim individuals to remain steadfast and endure various life challenges.